Modulation of electrical properties in MoTe2 by XeF2-mediated surface oxidation. Issue 4 (27th January 2022) - Ji, Eunji; Kim, Jong Hun; Lee, Wanggon; Shin, June-Chul; Seo, Hyungtak; Ihm, Kyuwook; Park, Jin-Woo; Lee, Gwan-Hyoung
Abstract : Transition metal dichalcogenides (TMDs) are promising candidates for the semiconductor industry owing to their superior electrical properties. Abstract : Transition metal dichalcogenides (TMDs) are promising candidates for the semiconductor industry owing to their superior electrical properties. Their surface oxidation is of interest because their electrical properties can be easily modulated by an oxidized layer on top of them. Here, we demonstrate the XeF2 -mediated surface oxidation of 2H-MoTe2 (alpha phase MoTe2 ). MoTe2 exposed to XeF2 gas forms a thin and uniform oxidized layer (∼2.5 nm-thick MoO x ) on MoTe2 regardless of the exposure time (within ∼120 s) due to the passivation effect and simultaneous etching. We used the oxidized layer for contacts between the metal and MoTe2, which help reduce the contact resistance by overcoming the Fermi level pinning effect by the direct metal deposition process. The MoTe2 field-effect transistors (FETs) with a MoO x interlayer exhibited two orders of magnitude higher field-effect hole mobility of 6.31 cm 2 V −1 s −1 with a high on/off current ratio of ∼10 5 than that of the MoTe2 device with conventional metal contacts (0.07 cm 2 V −1 s −1 ). Our work shows a straightforward and effective method for forming a thin oxide layer for MoTe2 devices, applicable for 2D electronics.